Risk Factors of Suicide Death Based on Psychological Autopsy Method; a Case-Control Study - Nafee Rasouli; Seyed Kazem Malakouti; Mohsen Rezaeian; Seyed Mehdi Saberi; Marzie Nojomi; Diego De Leo; Abbas Ramezani-Farani (Archives of Academic Emergency Medicine, 2019)
Introduction: Investigation in each community can contribute to understanding the key factors involved in suicide death and its prevention. The present study aimed to investigate suicide death risk factors based on psychological autopsy method.